PENGARUH TINGKAT PENDIDIKAN DAN TINGKAT KESEHATAN TERHADAP PRODUKTIVITAS TENAGA KERJA DI PROVINSI SUMATERA BARAT - Hanif Hanif; Nadia Rista (Aliansi : Jurnal Manajemen dan Bisnis, 2019)
This study aims to determine 1) Effect of Education Level on Labor Productivity in West Sumatera 2) Effect of Health Level on Labor Productivity in West Sumatera 3) Influence together education level and level of health to Labor productivity in West Sumatra. The type of this research is descriptive and associative. The type of data used pooling or panel. Data analysis techniques, namely descriptive and inductive analysis. Inductive analysis includes 1) Hausman Test 2) Chow-Test 3) Analysis of Panel Regression Model, selected result on REM. To see the significance of the effect of independent variables on dependent variable used 1) Test t and 2) Test F with 5% real level. The results of the research are (1) Educational level has a significant and positive effect on labor productivity in West Sumatra. with value (prob = 0.0000 á = 0,05), (2) Health level have a significant and positive effect to labor productivity in West Sumatera (prob = 0.0000 á = 0,05).